Formulation of Spray-dried Proliposomes Loaded with Berberin - Thi Hai Yen, Tran; Thi Nhu Quynh, Tran; Thi Thuan, Duong; Thi Minh Hue, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
The aims of study was formulation and evaluation of berberin (BBR) loaded proliposomes by spray-drying method. BBR proliposomes were evaluated for appearance, spray-drying efficiency, morphology and differential scanning calorimetry (DSC). Liposomes, obtained after hydration, were evaluated for particle size, size distribution, morphology and entrapment efficiency. The results showed that BBR proliposomes were prepared by spray-drying method with molar ratio of Hydrogenated soy phosphatidyl choline (HSPC): Sodium deoxycholat (NaDC): vitamin E (vtE): BBR = 7: 1: 6: 6. Mixture of manitol and Aerosil at weight ratio of 97:3 was used as carrier. Results of DSC showed that berberin was dispersed molecularly into proliposomes powder. BBR liposomes, obtained after hydration, had average particle diameter of about 29 μm and entrapment efficiency was 22.23%. Keywords Proliposomes, liposomes, berberin, sodium deoxycholate, spray-dried. References [1] W. Kong, J. Wei, A. Parrveen et al., Berberine is A Novel Cholesterol-Lowering Drug Working Through A Unique Mechanism Distinct From Statins, Nature Medicine, Vol. 10, No. 12, 2004, pp. 1344-1351, https://doi.org/10.1038/nm1135. [2] S. K. Kulkarni, A. Dhir, on The Mechanism of Antidepressant-Like Action of Berberine Chloride, European Journal of Pharmacology, Vol. 589, No. 1-3, 2008, pp. 163-172, https://doi.org/ 10.1016/j.ejphar.2008.05.043. [3] Y. T. Ho, J. S. Yang, T. C. Li et al., Berberine Suppresses in Vitro Migration and Invasion of Human SCC-4 Tongue Squamous Cancer Cells Through the Inhibitions of FAK, IKK, NF-Κb, U-PA and MMP-2 and-9, Cancer Letters, Vol. 279, No. 2, 2009, pp. 155-162, https://doi.org/10.1016/j.canlet.2009.01.033. [4] S. Muneer, Z. Masood, S. Butt et al., Proliposomes as Pharmaceutical Drug Delivery System: A Brief Review, Journal of Nanomedicine and Nanotechnology, Vol. 8, No. 3, 2017, pp. 448-450, https://doi.org/10.4172/2157-7439.1000448. [5] H. K. Omer, N. R. Hussein, A. Ferraz et al., Spray-Dried Proliposome Microparticles for High-Performance Aerosol Delivery Using a Monodose Powder Inhaler, AAPS PharmSciTech, Vol. 19, No. 5, 2018, pp. 2434-2448, https://doi.org/10.1208/s12249-018-1058-4. [6] T. T. H. Yen, T. T. N. Quynh, D. T. Thuan, P. T. M. Hue, Preparation of Berberin Liposomes, Contained Sodium Deoxycholate by Ethanol Injection Method, Journal of Pharmaceutical Research and Drug information, Vol. 11, No. 4, 2020, pp. 11-17 (in Vietnamese). [7] T. T. H. Yen, T. T. Hue, P. T. M. Hue et al., Preparation of Berberin Proliposomes by Film Deposition on Carrier Surface Method, VNU Journal of Science: Medical and Pharmaceutical Sciences, Vol. 36, No. 2, 2020, pp. 9-15, https://doi.org/10.25073/2588-1132/vnumps.4204. [8] R. G. Ahmed, S. Sherif, Z. Zainab et al., Silymarin Spray-Dried Proliposomes: Preparation, Characterization and Cytotoxic Evaluation, Drug Delivery Letters, Vol. 10, No. 1, 2020, pp. 14-23, https://doi.org/10.2174/2210303109666190722114211. [9] A. Bangham, M. M. Standish, J. C. Watkins Diffusion of Univalent Ions Across the Lamellae of Swollen Phospholipids, Journal of Molecular Biology, Vol. 13, No. 1, 1965, pp. 238-252.